Intramolecular Diels Alder-ROM-RCM approach towards the synthesis of triquinanes, and, Magnesium mediated carbometallation-annulation for the synthesis of fused rings - Nguyen, Natalie N. M (University of Ottawa (Canada), 2005)
In recent years, there has been a shift in focus in organic synthetic chemistry, steering away from multistep synthesis, leaning towards tandem and one pot reactions. Described herein is a unique, one pot method for the synthesis of linear triquinanes. The strategy involved a one pot intramolecular Diels-Alder---ring opening metathesis---ring closing metathesis sequence to form triquinane 85. Application of the new methodology towards the synthesis of antibiotic Delta(9,12)- capnellene (13) was performed. During our endeavors, the core ring structure 86 was synthesized.* Also described is a second project which involved the synthesis of bicyclic compounds through a new carbometallation-annulation reaction. The reaction was used for the synthesis of dihydrophenanthrene 129 and chiral tricycle 137. Insight into the application to the synthesis of indoles was also investigated.* *Please refer to dissertation for diagrams.
Keywords: Chemistry, Organic.